A history of Indian poetry in English - Chaudhuri, Rosinka
"A History of Indian Poetry in English explores the genealogy of Anglophone verse in India from its nineteenth-century origins to the present day. Beginning with an extensive introduction that charts important theoretical contributions to the field, this History includes extensive essays that illuminate the legacy of English in Indian poetry. Organized thematically, these essays survey the multilayered verse of such diverse poets as Henry Louis Vivian Derozio, Rabindranath Tagore, Ezekiel Moraes, Kamala Das, and Melanie Silgardo. Written by a host of leading scholars, this History also devotes special attention to the lasting significance of imperialism and diaspora in Indian poetry. This book is of pivotal importance to the development of Indian poetry in English and will serve as an invaluable reference for specialists and students alike"--